Our Sun: Grigorii Dashevskii Has Died: Obituary. (2nd January 2019) - Stepanova, Maria
Abstract : Grigorii Dashevskii (1964-2013) was a poet, translator, and literary critic. In this obituary from the Russian newspaper Kommersant, his friend and fellow poet Maria Stepanova describes him as a person and a creative personality.